Novel guanidinylated bioresponsive poly(amidoamine)s designed for short hairpin RNA delivery - Yu J (Dove Medical Press, 2016)
Jiankun Yu,1 Jinmin Zhang,1 Haonan Xing,1 Yanping Sun,1 Zhen Yang,1 Tianzhi Yang,2 Cuifang Cai,1 Xiaoyun Zhao,3 Li Yang,1 Pingtian Ding1 1School of Pharmacy, Shenyang Pharmaceutical University, Shenyang, China; 2Department of Basic Pharmaceutical Sciences, School of Pharmacy, Husson University, Bangor, ME, USA; 3Department of Microbiology and Cell Biology, School of Life Science and Biopharmaceutics, Shenyang Pharmaceutical University, Shenyang, China Abstract: Two different disulfide (SS)-containing poly(amidoamine) (PAA) polymers were constructed using guanidino (Gua)-containing monomers (ie, arginine [Arg] and agmatine [Agm]) and N,N'-cystamine bisacrylamide (CBA) by Michael-addition polymerization. In order to characterize these two Gua-SS-PAA polymers and investigate their potentials as short hairpin RNA (shRNA)-delivery carriers, pSilencer 4.1-CMV FANCF shRNA was chosen as a model plasmid DNA to form complexes with these two polymers. The Gua-SS-PAAs and plasmid DNA complexes were determined with particle sizes less than 90 nm and positive ζ-potentials under 20 mV at nucleic acid:polymer weight ratios lower than 1:24. Bioresponsive release of plasmid DNA was observed from both newly constructed complexes. Significantly lower cytotoxicity was observed for both polymer complexes compared with polyethylenimine and Lipofectamine 2000, two widely used transfection reagents as reference carriers. Arg-CBA showed higher transfection efficiency and gene-silencing efficiency in MCF7 cells than Agm-CBA and the reference carriers. In addition, the cellular uptake of Arg-CBA in MCF7 cells was found to be higher and faster than Agm-CBA and the reference carriers. Similarly, plasmid DNA transport into the nucleus mediated by Arg-CBA was more than that by Agm-CBA and the reference carriers. The study suggested that guanidine and carboxyl introduced into Gua-SS-PAAs polymers resulted in a better nuclear localization effect, which played a key role in the observed enhancement of transfection efficiency and low cytotoxicity. Overall, two newly synthesized Gua-SS-PAAs polymers demonstrated great potential to be used as shRNA carriers for gene-therapy applications. Keywords: short hairpin RNA, gene carrier, bioresponsive, guanidinylated disulfide-containing poly(amido amine), nuclear localization, transfection efficiency, cytotoxicity